Study on Vernacular Architecture Patterns to Improve Natural Ventilation Estimating in Humid Subtropical Climate - Abdollah Baghaei Daemei; Parisa Haghgooy Osmavandani; Maede Samim Nikpey (Salehan Institute of Higher Education, 2018)
Wind ventilation is an efficient design strategy for the natural cooling system (NCS) in humid climates. The building forms can generate different pressures and temperatures to induce natural ventilation. This study has been carried out in Rasht city, Iran in 2017. The method was performed using a computational fluid dynamic (CFD) approach simulation to study variance between the proposed and the actual results of a design. The goal of the study is to assist architects to design optimum building form for natural ventilation. Hence, the purpose of this study was to investigate the effect of the form on natural ventilation. On this basis, wind flow simulation was performed using Design Builder Version 4.5. In this paper, the present usage of natural ventilation of rural residential buildings in Rasht area the application of this methodology. Initially, wind simulation was carried out based on actual building specifications. Then the proposed L-shaped extension was added to the building. The results showed that if the rectangular form is turned into an L shape, it can offer a better flow pattern for wind in all rooms, but the speed will be reduced.